Exploring good mental health for people with intellectual disabilities: a qualitative interview study with mental health experts - Sophie Komenda-Schned; Paula Moritz; Sarah Jasmin Landskron; Alma Rosa Herscovici; Charlotte Schomburg; Julia Lehner; Brigitte Lueger-Schuster; Luis Salvador-Carulla; Elisabeth Lucia Zeilinger (International Journal for Equity in Health)
Abstract Background Most mental health research focuses on mental disorders, with a paucity of studies exploring good mental health. Widely used definitions of good mental health (e.g., WHO’s) include several aspects of positive human functioning as predisposing to mental health. According to diagnostic criteria, people with intellectual disabilities (ID) are impaired in their functioning levels (e.g., intellectual functioning, adaptive skills). Existing definitions of good mental health may therefore not be applicable to an ID population. Objective We aimed to explore the perspectives of experts on good mental health in people with ID to shed light on the constitutive factors of good mental health in this population. Methods Semi-structured expert interviews with open-ended questions (N = 12) were conducted with psychiatrists, psychologists, psychotherapists, and psychiatric nurses, working either academically or in practice with this population. Inductive, reflexive thematic analysis was applied to analyze and synthesize the data. Results Four themes regarding components of good mental health in people with ID were derived: (1) Absence of Mental Illness, (2) Physical Health, (3) Psychosocial Functioning, and (4) Social Environment. Psychosocial functioning was divided into five subthemes, namely: (1) Emotional Competence, (2) Self-Concept, (3) Experience of Meaning, (4) Self-Determination, and (5) Personal Growth. Conclusions According the participants of this study, the constitutive factors of good mental health are similar for people with and without ID. The importance of needs-based, individualized support and an appropriate social environment was particularly emphasized for people with ID, to facilitate positive human functioning and promote good mental health.